AGRO-ECOLOGICAL ASSESSMENT OF IRRIGATED TOMATOES PRODUCTIVITY IN CONDITIONS OF CLIMATE WARMING - Polevoy, A. M.; Bozhko, L. E.; Barsukova, E. A.; Tolmachova, A. V. (Scientific Progress & Innovations, 2021)
This article presents the study results of the formation of irrigated tomatoes productivity in the Southern Steppe regions of Ukraine in the conditions of climate warming. The assessment of the impact of climate warming and irrigation rates on tomato productivity was performed based on comparing agro-ecological conditions of two periods: the first – 1961–1995, the second – 1996–2015. Calculations were performed us-ing the model of assessing agro-climatic conditions of crop productivity formation proposed by A. M. Pol'ovyy. It has been established that during the whole vegetation period of tomatoes the average air temperatures values per decade were higher by 1.2–1.3 °С on the average during the period from 1995 to 2015 than during the period of 1961–1995. Deviations from the second decade of July till the third decade of September were especially noticeable, as the temperatures for the second period were by 1.9–2.2 °С higher. The average amount of precipitation per decade during the growing season of tomatoes decreased slightly in the second period – by 13 mm. Given that the rates of irrigation were the same in both periods and averaged to 3,500 m3/ha, a slight decrease in rainfall did not cause the deterioration of plants’ moisture supply. Ele-vated temperatures throughout the growing season in the second study period led to an increase in total evaporation levels. This increase is especially noticeable starting from the fourth decade of the growing sea-son. Elevated air temperatures and good moisture content of crops in the second study period resulted in the tomatoes dry weight increase. Throughout the growing season, the increase in dry matter per decade during the second period was much higher than during the first, resulting in the increased vegetable yield. Calcula-tions of tomato productivity at different irrigation rates in the second period have allowed to establish that, under the conditions of warming, water consumption per total evaporation increases and the highest values of tomatoes’ dry weight is accumulated at the irrigation rate of 4,000 m3/ha. During the first period, maxi-mum increases were observed at irrigation rates of 3,500 m3/ha. In case of increasing the irrigation rate to 4,500 m3/ha, soil waterlogging occurs, which negatively affects the formation of vegetable yields, leads to the development of plant diseases, vegetable rot, worsening their quality. This confirms the opinion of lead-ing scientists that the optimal rate of irrigation for tomatoes is the rate at which the ratio of total evapora-tion volume to evaporation level is 0.8–0.9 relative units.